The Antarctic ozone hole during 2011 - Andrew Klekociuk; Tully, MB; Krummel, PB; Gies, HP; Petelina, SV; Simon Alexander; Deschamps, LL; Fraser, PJ; Henderson, SI; Javorniczky, J; Shanklin, JD; Siddaway, JM; et al. (2014)
The Antarctic ozone hole of 2011 is reviewed from a variety of perspectives, making use of various data and analyses. The ozone hole of 2011 was relatively large in terms of maximum area, minimum ozone level and total ozone deficit, being ranked amongst the top ten in terms of severity of the 32 ozone holes adequately characterised since 1979. In particular, the estimated integrated ozone mass effectively removed within the ozone hole of 2011 was 2119 Mt, which is the 7th largest deficit on record and 82 per cent of the peak value observed in 2006. The key factors in promoting the extent of Antarctic ozone loss in 2011 were the relatively low temperatures that occurred in the lower stratosphere of the polar cap region over most of the year, and the fact that the stratospheric vortex was relatively strong and stable, at least up to mid-spring. Dynamical disturbance of the polar vortex from mid-spring increased Antarctic ozone levels in the latter part of the ozone hole’s evolution and helped to limit the overall severity of depletion. Through examination of regression of various ozone metrics against expected levels of equivalent effective stratospheric chlorine, we suggest that recent changes in averaged ozone levels over Antarctica show some evidence of the recovery expected due to international controls on the manufacture of ozone depleting chemicals, albeit at a statistically low level of confidence due to the influence of meteorological factors that largely dictate year-to-year variability of Antarctic ozone loss.